Conceptualisation of the 'good' self-manager: A qualitative investigation of stakeholder views on the self-management of long-term health conditions. (March 2017) - Ellis, J.; Boger, E.; Latter, S.; Kennedy, A.; Jones, F.; Foster, C.; Demain, S.
Abstract: Healthcare policy in developed countries has, in recent years, promoted self-management among people with long-term conditions. Such policies are underpinned by neoliberal philosophy, as seen in the promotion of greater individual responsibility for health through increased support for self-management. Yet still little is known about how self-management is understood by commissioners of healthcare services, healthcare professionals, people with long-term conditions and family care-givers. The evidence presented here is drawn from a two-year study, which investigated how self-management is conceptualised by these stakeholder groups. Conducted in the UK between 2013 and 2015, this study focused on three exemplar long-term conditions, stroke, diabetes and colorectal cancer, to explore the issue. Semi-structured interviews and focus groups were carried out with 174 participants (97 patients, 35 family care-givers, 20 healthcare professionals and 22 commissioners). The data is used to demonstrate how self-management is framed in terms of what it means to be a 'good' self-manager. The 'good' self-manager is an individual who is remoralised; thus taking responsibility for their health; is knowledgeable and uses this to manage risks; and, is 'active' in using information to make informed decisions regarding health and social wellbeing. This paper examines the conceptualisation of the 'good' self-manager. It demonstrates how the remoralised, knowledgeable and active elements are inextricably linked, that is, how action is knowledge applied and how morality underlies all action of the 'good' self-manager. Through unpicking the 'good' self-manager the problems of neoliberalism are also revealed and addressed here. Highlights: Self-management is framed in terms of what it means to be the 'good' self-manager. Neoliberal health discourse is evident in conceptualisations of self-management. The 'good' self-manager is remoralised, knowledgeable and active. These three aspects are linked-action is knowledge applied and morality underpins both.